A conceptual framework for land use and metro infrastructure. Issue 4 (4th November 2016) - Darroch, Nathan; Beecroft, Mark; Nelson, John D.
Abstract : The continued urbanisation of the world's population generates pressures for the greater use of urban space. Where underground metro infrastructure is present within the urban environment, interfaces with private property at the surface and subsurface levels can raise issues from both engineering and legal perspectives. This paper introduces a conceptual framework for describing three principal interfaces identified as presence, property and protection. These three interfaces are interconnected and interdependent, each having three subinterfaces. The conceptual framework provides a way to determine these interfaces. The paper presents a proof-of-concept case study based on the Glasgow subway. It concludes that while the three overriding principal interfaces within the conceptual framework are applicable to any one metro system, not all subinterfaces may be.